Content Analysis for Critical Thinking Skills in the Lower Primary School Science Textbooks in Malaysia - Mai, Mohammed Y. M.; Yusuf, Muhammed; Saleh, Maria (European Journal of Social Science Education and Research, 2024)
The purpose of this study is to analyse lower primary science textbooks (grade 1-3), which were implemented by the Ministry of Education in Malaysia, in terms of thinking skills. To achieve this, a tool for content analysis including thinking skill items will be constructed. Two science teachers have be trained to conduct the content analysis for grade 1-3 science textbooks, the reliability and validity of analysis have be verified using Cohen’s kappa statistic. From the results, it can be seen clearly that Prioritizing”, “Evaluation” and “Detecting Bias” thinking skills are not included at all in the science textbook from year one until year three. While, the most frequent critical thinking skills are “attributing”, “analysing”, “Grouping and Classifying” and “Sequencing” gradually. Most of the skills have been in the pictures for year one, and in the “text” and then within the “picture” and finally within the “activities” for both of year two and three. Such research help teachers and curriculum developers in the development and implementation of science curriculum to raise the level of achievement of thinking skills for students.Keyword: Thinking Skills, Critical Thinking Skills, Content Analysis and Science Textbooks